2016
DOI: 10.3892/etm.2016.3489
|View full text |Cite
|
Sign up to set email alerts
|

Curettage after uterine artery embolization combined with methotrexate treatment for caesarean scar pregnancy

Abstract: In the present study, we evaluated the diagnosis and management modalities of caesarean scar pregnancy (CSP). Thirty patients diagnosed with CSP were retrospectively studied between February, 2010 and February, 2012. Twenty-five patients were offered prophylactic uterine artery embolization (UAE) and methotrexate (MTX) prior to uterine suction curettage. Five cases were referred from other hospitals where the initial management with uterine suction curettage had resulted in uncontrollable massive haemorrhage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
(51 reference statements)
2
15
0
Order By: Relevance
“…Vascular occlusion with gelfoam causes acute necrotizing arteritis. [ 18 ] UAE followed by surgery is widely used by doctors because it is safe and effective. The inflammatory process of UAE eventually leads to the breakdown of the gelfoam within 1 to 3 weeks after embolization with subsequent vascular recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular occlusion with gelfoam causes acute necrotizing arteritis. [ 18 ] UAE followed by surgery is widely used by doctors because it is safe and effective. The inflammatory process of UAE eventually leads to the breakdown of the gelfoam within 1 to 3 weeks after embolization with subsequent vascular recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…The reduce of uterine blood supply by UAE was impermanently, since the gelfoam could be resolved within 7-14 days. Depending on this mechanism, most authors theoretically suggested that curettage should be taken within 24-72 hours after UAE to balance the bene t of onset time and the risk of recanalization [5][6][7][8][9][10][11]. Currently, it is only a clinical opinion which still needs reliable clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…However, the timing of curettage after UAE remains to be studied. In previously reported studies, the time intervals between UAE and curettage were quite different, ranging from 24 to 72 hours [5][6][7][8][9][10][11]. There is no consensus on the optimal time interval to perform curettage after UAE.…”
Section: Introductionmentioning
confidence: 99%
“…As a non-invasive therapy, recent studies have demonstrated that UAE can block uterine artery blood flow, which results in trophoblastic cell degeneration and necrosis ( 17 ). UAE, in combination with drugs or curettage, can achieve better curative effects ( 18 , 19 ). A study revealed that the gestational age of CSP is >8 weeks, and a CSP mass of ≥6 cm tends to have an unsatisfactory outcome after UAE, followed by curettage ( 20 ).…”
Section: Discussionmentioning
confidence: 99%